ENHANCING THE ROLE OF THE FINANCIAL DIGITAL VOLUNTEER IN OVERCOMING THE PANDEMIC BY THE POPULATION OF RURAL AREAS - V. Manuylenko; M. Yevglevskaya (Вестник Северо-Кавказского федерального университета)
In the context of the instability caused by the global pandemic, the rural population needs overcome both the restrictions imposed as part of the fight against the global pandemic and their economic consequences, a key role in this process belongs to financial digital volunteers. The purpose of the study i to determine the role of the financial digital volunteer in overcoming the pandemic by the population ofrural areas. The study examines its functions, principles, and main areas of activity that ensure the development of financial digital competencies by the rural population, calculates the financial literacy index, which reflects the ability of a person to optimally manage personal inances, including rural ones; expands programs for concessional lending through the restructuring of loans at acceptable rates. As a result, the role of the inancial digital volunteer is determined, on the one hand, in overcoming the general pandemic by the population of rural areas, and, on the other hand, in ensuring the development of digitalization.